Sintesis Biodiesel Dari Minyak Nyamplung Menggunakan Katalis Geopolimer: Pengaruh Suhu Reaksi Transesterifikasi Dan Rasio Mol Minyak Terhadap Metanol - Abdullah Syafi’i; Edy Saputra; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Petroleum reserves in Indonesia are increasingly depleted, requiring the use of alternative energy that is environmentally friendly and renewable like biodiesel. Biodiesel can be made by transesterification process of vegetable oils. Process of making biodiesel commonly use homogeneous catalyst which has the disadvantage the formation of by products such as complexity of the separation of catalyst. Therefore, in this study biodiesel was synthesized from calophyllum inophyllum oil by using geopolymer catalyst. Geopolymer catalyst is first synthesized by reacting sodium silicate, metakaolin, NaOH, and water. Several variations of the process variables were done to assess its influence on yield of biodiesel. The variables were used consist of a dependent variables and independent variables. The dependent variables were calophyllum inophyllum oil weight of 50 grams, 3%-wt of catalyst concentration, reaction time of 120 minutes, and stirring speed of 400 rpm, while the independent variables which variation molar ratio of oil:methanol 1:6 and 1:9 and variations of temperature 55 and 65 oC. Physical characterization were done including density 871 kg/m3, kinematic viscosity 4.38 mm2/s, acid number 0.41 mg-KOH/g biodiesel and flash point 140°C respectively accordance with the standards of Indonesian biodiesel (SNI 7182:2015).Keywords: biodiesel, catalyst, calophyllum inophyllum oil, geopolymer, yield